Polybenzimidazole / tetrazole-modified poly(arylene ether) blend membranes for high temperature proton exchange membrane fuel cells - Krishnan, N. Nambi; Duong, Ngoc My Hanh; Konovalova, Anastasiia; Jang, Jong Hyun; Park, Hyun S.; Kim, Hyoung Juhn; Roznowska, Aleksandra; Michalak, Artur; Henkensmeier, Dirk (ELSEVIER, 2020)
Poly(arylene ether)s containing 5-phenyl tetrazole (Tz) and either biphenyl (TzPN) or more flexible phenoxyphenyl (TzPEN) in the backbone were synthesized and blended in different ratios with mPBI, to benefit from the good ratio of conductivity to phosphoric acid (PA) uptake reported for Tz functionalized polymers, and from the high PA uptake and high mechanical strength of mPBI. Blend membranes containing 25 wt% TzPN and TzPEN had PA uptakes of 440 and 322%, respectively, in comparison to 505% for mPBI, but showed higher conductivities at 160 degrees C: 189 for mPBI-TzPN25, 195 for mPBI-TzPEN25, but just 147 mS cm(-1) for mPBI. Most importantly, a PA doped mPBI-TzPEN25 membrane showed an initial peak power density of 447 mW cm(-2), while the peak power density of mPBI was just 348 mW cm(-2). The voltage at 0.2 mA cm(-2) was 0.69 V, which is one of the highest reported values for post-doped membranes. When tested for 2400 h, the OCV of mPBI-TzPEN25 dropped only from 963 mV at the begin to 937 mV at the end of test, indicating that the membrane did not form defects. Over the last 2000 h, the cell was operated at very challenging 800 mA cm(-2). The linear voltage decrease was just 27.7 mu V h(-1). Calculations indicate that TZ-PN and TZ-PEN can form chains of hydrogen-bonded TZ units, and low proton-transfer barriers suggest the possibility that the proton conduction mechanism could also partially involve proton hopping involving the tetrazole groups.